2015
DOI: 10.1155/2015/235101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiovascular Disease and Associated Risk Factors among Adult Population in the Gulf Region: A Systematic Review

Abstract: Background. CVD is a principal cause of mortality and disability globally.Objective. To analyse the epidemiological data on CHD, strokes, and the associated risk factors among adult population in the Gulf countries.Methods. A systematic review of published articles between 1990 and 2014 was conducted.Results. The analysis included 62 relevant studies. The prevalence of CHD was reported to be 5.5% in Saudi Arabia. The annual incidence of strokes ranged from 27.6 to 57 per 100 000 in the Gulf countries with isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
198
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(212 citation statements)
references
References 69 publications
(171 reference statements)
14
198
0
Order By: Relevance
“…This is similar to results published by The American Heart Association and other studies [4][5][6]. However, one study reported higher rates of CAD in females [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to results published by The American Heart Association and other studies [4][5][6]. However, one study reported higher rates of CAD in females [6].…”
Section: Discussionsupporting
confidence: 91%
“…Aljefree and Ahemed reported that the prevalence of cardio vascular diseases (CVD) in Saudi Arabia is 5.5% and hypertension, diabetes mellitus (DM), obesity, smoking and poor dietary habits were risk factors for the CVD in the Gulf region [5]. Sarvotham [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, measurement of the level(s) of one or more specific cardiac biomarkers is used to determine the extent of myocardial damage and to assess a patient's prognosis. Historically, creatine kinase (CK), CK-MB, CK mass, and lactate dehydrogenase have 2 been used for routine clinical management. 5 Creatine kinase-MB (CK-MB) is found mostly in heart muscles.…”
Section: Introductionmentioning
confidence: 99%
“…It is also considered as the major cause of death in the Kingdom of Saudi Arabia [2][3][4] .According to the literature [2][3][4] , the burden of hypertension remained very high in KSA from 1990 to 2010; the number of deaths resulting from ischemic heart disease and hypertensive heart disease in the Middle East and North Africa region (including the GCC countries) is estimated to be 294/100,000 and 115/100,000 respectively; and the number of disability-adjusted life years (DALYs) resulting from ischemic and hypertensive heart disease is 3702/100,000 and 1389/100,000, respectively, in the same region. These studies further state that KSA has a young population with 81% of the population under the age of 40 and life expectancy has increased from 72.5 and 76.3 years in 1990 to 75.0 and 79.9 years in 2010 for men and women, respectively.…”
Section: Introductionmentioning
confidence: 99%